A high-gain, low-noise 3.1â10.6 GHz ultra-wideband LNA in a 0.18Î¼m CMOS - Hamid Nooralizadeh; Behnam Babazadeh Daryan (Majlesi Journal of Electrical Engineering)
An ultra-wideband (UWB) common gate-common source (CG-CS) low-noise amplifier (LNA) in a 0.18Î¼m CMOS technology is presented in this paper. To obtain a high and flat power gain with low noise and good input impedance matching in the entire 3.1â10.6 GHz UWB band among low power consumption, a capacitive cross-coupling fully differential amplifier with the current-reuse technique is proposed. The currentâreuse technique is used to achieve a wideband and reduce power consumption. The capacitor cross coupling technique is used to gm-boosting and hence to improve the NF of the amplifier. Therefore, the dependency between noise figure (NF) and input impedance matching is reduced. The proposed CG-CS amplifier has a fairly low NF compared with the other previous works in similar technology. In addition, a good power gain over all bandwidth and a high isolation with good input/output impedance matching are achieved. The minimum NF is 1.8 dB, the maximum power gain is 14.2 dB, the inverse gain is